Penggunaan Metode Muhadatsah Dalam meningkatkan prestasi belajar Santriwati pada pembelajaran Bahasa Arab Di Madrasah Aliyah (MA) Pondok pesantren Moderen Darul Mahfudz Lekopadis - M.D, Hariawan; Ridha, Ahmad; Durusming, Amira Handayani Mandar (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2022)
The purpose of this study was to determine the use of the Muhadatsah method in increasing student achievement in learning Arabic at Madrasah Aliyah (MA) Pondok pesantren Moderen Darul Mahfudz Lekpadis. This type of research is classroom action research (PTK) which is designed in two cycles. The instruments used in this research were the teacher and student activity observation sheets and test sheets. Data collection techniques using observation and tests. The data analysis technique used qualitative descriptive analysis and quantitative descriptive analysis. The results showed that there was an increase in student achievement from cycle I, which can be seen from the results of the learning test, namely from 18 students in cycle 1 who completed 14 students with a percentage of 80% completeness and had not fulfilled classical completeness. So it can be concluded that the use of the Muhaddatsah method can improve Student Achievement in Learning Arabic at Madrasah Aliyah (MA) Pondok pesantren Moderen Darul Mahfudz Lekopadis.